2000
DOI: 10.1099/00221287-146-1-209
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of Pleurotus species according to the sequence and secondary structure of the mitochondrial small-subunit rRNA V4, V6 and V9 domains The GenBank accession numbers for the sequences reported in this paper are given in Methods.

Abstract: A comparative study of the V4, V6 and V9 domains of the mitochondrial smallsubunit (SSU) rRNA was conducted to evaluate the use of these sequences to investigate phylogenetic relatedness within the genus Pleurotus. The PCR products encompassing these regions from 48 isolates belonging to 16 Pleurotus species were sequenced and compared. From this comparison, the length and sequence of the three domains were found to be constant within a species. Significant inter-species variations due to insertion/deletion ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…In general, the parsimonious trees deriving from isozyme or RAPD-PCR and from combined isozyme and RAPD-PCR data were very similar to each other, confirming the agreement of the approaches. In contrast, previous phylogenetic studies demonstrated that the use of additional molecular characters such as the mitochondrial smallsubunit rRNA and\or of the nuclear rRNA ITS sequences were of particular value only above the species level (Gonzalez & Labare' re, 2000 ;Wu et al, 2000 ;Vilgalys & Sun, 1994).…”
Section: Evaluation Of the Biochemical And Molecular Datamentioning
confidence: 64%
“…In general, the parsimonious trees deriving from isozyme or RAPD-PCR and from combined isozyme and RAPD-PCR data were very similar to each other, confirming the agreement of the approaches. In contrast, previous phylogenetic studies demonstrated that the use of additional molecular characters such as the mitochondrial smallsubunit rRNA and\or of the nuclear rRNA ITS sequences were of particular value only above the species level (Gonzalez & Labare' re, 2000 ;Wu et al, 2000 ;Vilgalys & Sun, 1994).…”
Section: Evaluation Of the Biochemical And Molecular Datamentioning
confidence: 64%
“…Under varying climate conditions different ecotypes of Pleurotus mushrooms have become established, among which commercially important ones include the following: P. ostreatus (oyster mushroom), P. eryngii (king oyster mushroom), Pleurotus djamor (pink oyster mushroom), Pleurotus citrinopileatus (golden oyster mushroom), Pleurotus florida (white oyster mushroom), and Pleurotus pulmonarius (Indian Oyster, Phoenix Oyster). However, phylogenetic studies have demonstrated that some of them, e.g., P. ostreatus and P. florida, represent in fact a single species (Gonzalez and Labarere 2000). The abovementioned common names are used in trade.…”
Section: Introductionmentioning
confidence: 99%
“…Recent molecular phylogenetic analysis of Pleurotus provides a useful framework for understanding species concepts and taxonomy. Relationships between species and species determination have also been studied, and the results of systematic analyses of LSU and ITS sequences in nuclear rDNA (42,43,50) and of small-subunit sequences in mitochondrial rDNA (8) show that ITS sequences are an ideal marker for species identification. A large number of ITS sequences from this genus have been accumulated, and a molecular identification method using the PCR-RFLP technique to distinguish Pleurotus species can be developed through the DNA sequence analyses.…”
mentioning
confidence: 99%